Peatlands as geo-archives for atmospheric micro- and nano-plastics: a perspective review - Rahimpouri, Arman; Abbasi, Sajjad; Dzingelevičius, Nerijus; Dzingelevičienė, Reda (Frontiers in Earth Science, 2025)
Since commercial manufacture of plastics started around 1950, plastics have grown more and more important to human society. The ubiquity of plastic particles in the environment and Inefficient waste management have led to the presence of tiny plastic particles in a wide range of natural matrices. Nowadays, finding natural environments with the most potential to archive the past deposition of airborne microplastics is among the hot research topics while investigating plastic pollution across the globe. The capability of peatlands as the most widespread type of wetlands throughout the earth to illustrate natural and anthropogenic deposition of different contaminants has drawn the attention of researchers in recent years. A number of studies have been conducted on the presence and distribution of various pollutants in peatland areas. However, there is still limited information on the presence of microplastics in peatlands. The purpose of this study is to gather the existing data on the occurrence, deposition and distribution of microplastics in peatland areas. We have tried to examine the potential of peatlands as natural archives of atmospheric micro and nano plastics. The research indicates that peatlands serve as a reliable (with some uncertainties) geo-archive for atmospheric micro (nano) plastics. It thoroughly assesses various methods, from sampling to final analyses, to empower researchers in selecting the most effective approach.